El cuerpo, vector de una exclusión que activa la rentabilidad en organizaciones productivas (2019)
The following ideas have risen from qualitative social research. The data collected from the fieldwork was obtained from social actors, in a series of mid-structured and ethnographical interviews. They provide images and reasons that support the objectivation and domination of the body in business organizations; they also clarify who is involved in such practices and in what areas in the organization they take place. As far as the written sources, I considered the theoretical and practical trends of corporal objectivation that have prevailed in modern society. My interpretative view of the data resulted in an inventory of significant structures, sorted by descriptive categories, which emerged from the testimonies. Therefore, all the reflections and conjectures that provide form and sense to this manuscript have been inspired in the search of bibliographical sources, and in conversations with social actors. Strictly speaking, I point out circumstances and practices of corporal objectivation that came up in the data analysis; I have not further considered their significance, beyond what the interviewees’ own words allow to see. I only aspire to show, by a simple description, a certain relation between some theoretical elements of the problems studied, and testimonies of social actors interviewed in conversations. The intention of the aforementioned study was to approach the understanding of those practices used to represent, imagine and mold the body, in an effort of some organizations to make the productive setting grow. And the goal was to understand the objectivation of the body as a dispositive of power in organizations.